Analisis Pengembangan Objek Wisata Air Terjun Coban Glotak Sebagai Daya Tarik Wisata Di Desa Dalisodo, Kecamatan Wagir, Kabupaten Malang - Hambut, Silvanus; Primasworo, Rifky Aldila; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Dalisodo Village is well known in the community, especially in the world of tourism. This village is very rich in natural potential, located in Malang Regency, which is the center of a tourism center that is easy to reach. Coban Glotak waterfall is located in Dalisodo village as a very interesting potential tourist attraction. Coban Glotak Waterfall has a height of 100 m and is still in the Coban Glotak Forest so that it presents a balance system in human life. Coban Glotak waterfall should be developed as a tourist attraction that ultimately brings benefits to the local community. The roads are still damaged, the parking area is still not managed and maintained properly and there is no clear registration system. The data collection technique used purposive sampling with in-depth interviews with the village head, management, community and visitors. Existing data is processed using the SWOT technique by analyzing the situation then described in a conclusion to formulate a management strategy formula. Based on internal and external factors owned by Coban Glotak Waterfall, the following strategies can be formulated: improving cleanliness, promotional programs, building cooperation with tourism businesses and managing supporting facilities. From the results of the analysis obtained based on the results of the IFAS and EFAS SWOT matrix in the table as described above, the results can be summarized as follows: Coordinates of the internal analysis diagram (X) (Total Strength-Score Total Weakness) :2 = (3.5-3.4) : 2 = 1.8 Coordinates of external analysis (Y) (Total Opportunities-Score of Total Threats) : 2 = (2,7-2,9) : 2 = - 0,1.